Target Definition in Salvage Radiotherapy for Recurrent Prostate Cancer: The Role of Advanced Molecular Imaging - Amzalag, Gaël; Rager, Olivier; Tabouret-Viaud, Claire; Wissmeyer, Michael; Sfakianaki, Electra; de Perrot, Thomas; Ratib, Osman; Miralbell, Raymond; Giovacchini, Giampiero; Garibotto, Valentina; Zilli, Thomas (Frontiers in Oncology, 2016)
Salvage radiotherapy (SRT) represents the main treatment option for relapsing prostate cancer patients after radical prostatectomy (RP). Several open questions remain unanswered in terms of target volumes definition and delivered doses for SRT: the effective dose necessary to achieve biochemical control in the SRT setting may be different if the tumor recurrence is micro- or macroscopic. At the same time, irradiation of the prostatic bed only or of the whole pelvis will depend on the localization of the recurrence, local or loco-regional. In the “theragnostic imaging” era, molecular imaging using Positron Emission Tomography (PET) constitutes a useful tool for clinicians to define the site of the recurrence, the extent of disease and individualize salvage treatments. The best option currently available in clinical routine is the combination of radiolabelled choline PET imaging and multiparametric magnetic resonance imaging (MRI), associating the nodal and distant metastases identification based on PET and the local assessment by MRI. A new generation of targeted tracers, namely prostate specific membrane antigen (PSMA), show promising results, with a contrast superior to choline imaging and a higher detection rate even for low prostate specific antigen levels; validation studies are ongoing. Finally, imaging targeting bone remodeling using whole body SPECT-CT is a relevant complement to molecular/metabolic PET imaging when bone involvement is suspected.